I LOVE TEACHING: The reflective stories of English teachers at achieving shools in Banda Aceh - Khairil Razali; Teuku Zulfikar (Universitas Islam Negeri Banda Aceh, 2018)
The study explored the teachers teaching strategies in six high achieving schools in Banda Aceh. One main purpose of the study was to explore particular strategies teachers use in conducting teaching effectively. The study was approached using the qualitative classroom research. The settings of the study were six high achieving secondary schools in Banda Aceh. The data of the study were collected through in-depth semi-structured Interview, observation and also focus group discussion. The data which was analysed using coding techniques reveals that most teachers interviewed suggested that they feel teaching at schools was at ease, and this due to mostly their extensive teaching experiences, trainings and Students’ learning passion.